2010
DOI: 10.3382/ps.2009-00216
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E supplementation alleviates the oxidative stress induced by dexamethasone treatment and improves meat quality in broiler chickens

Abstract: In the present study, the effects of long-term exogenous glucocorticoids administration and dietary supplementation of alpha-tocopheryl acetate on the induction of lipid peroxidation in skeletal muscle were investigated. Male broiler chicks were randomly assigned to 2 diet treatments: the basal diet supplemented with 20 (low level of vitamin E) or 200 (high level of vitamin E) mg of vitamin E (as DL-alpha-tocopheryl acetate)/kg of diet. At 35 d of age, the chickens in each dietary treatment were randomly divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
68
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 38 publications
9
68
1
3
Order By: Relevance
“…These results suggest that breast and leg meat from the broilers that drank liquid antioxidants might have electron donors to neutralize free radicals, which is in agreement with results of a previous study (Jung et al, 2010). Many studies reported that chickens reared at a high temperatures had increased TBARS in plasma, organs, and carcass (Lin et al, 2000;Mahmoud and Edens, 2003;Gao et al, 2010). The supplementation of antioxidants prevented lipid oxidation in chicken meat that decreased TBARS value, which is a consequence of oxidant stress (Jung et al, 2010;Cortinas et al, 2005).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results suggest that breast and leg meat from the broilers that drank liquid antioxidants might have electron donors to neutralize free radicals, which is in agreement with results of a previous study (Jung et al, 2010). Many studies reported that chickens reared at a high temperatures had increased TBARS in plasma, organs, and carcass (Lin et al, 2000;Mahmoud and Edens, 2003;Gao et al, 2010). The supplementation of antioxidants prevented lipid oxidation in chicken meat that decreased TBARS value, which is a consequence of oxidant stress (Jung et al, 2010;Cortinas et al, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…E might improve lipid stability and reduce lipid oxidation in chicken meat (Cortinas et al, 2005). Gao et al (2010) demonstrated that the high level of vit. E was effective for the performance of broilers by reducing oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Using DEX as an artificial stress caused deterioration in most reproductive and physiological performance of birds such as male domestic fowls (Eid et al, 2006), laying quails (Aengwanich and Chinrasri, 2003) and pigeons (Westerhof et al, 1996). As shown recently, DEX administration produces large amounts of reactive species and is suggested to induce oxidative stress after treatment of broiler (Gao et al, 2010) and laying hens (El-Habbak et al, 2005;Eid et al, 2008). Many researches have been provided important information about how birds are affected by the elevated plasma corticosterone levels that occur during chronic stress (Calandreau et al, 2011;Gao et al, 2010;Lin et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…The National Research Council (1994) recommends that 10 mg of vitamin E/kg of diet be supplemented in basal diets of broiler chickens; however, levels 20 to 25 times higher have been used in the finisher phase (Barreto et al, 1999). Positive effects of diet supplementation with high levels of vitamin E (100 to 200 mg/kg) have been described on meat quality of chickens exposed to oxidative stress (Sahin et al, 2001;Gao et al, 2010), but growth performance was not always improved (Niu et al, 2009;Hazigawa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%